Barriers And Facilitators In Implementing Skin-To-Skin Contact After Birth: A Systematic Review - Fitriana, Farida (Jurnal Syntax Fusion, 2021)
Although the importance and benefit of Skin-to-Skin Contact (SSC) have been recognized universally and it is essential to support exclusive breastfeeding, it is often not performed because of many factors. The systematic review explored any barriers and facilitators in implementing Skin-to-Skin Contact (SSC) after birth. A literature search was performed using key terms: Skin-to-skin contact, Barrier, and Support and its synonyms through PubMed, Medline, CINAHL databases. The eligibility criteria of the reviewed article were published in the last five years, in English, and full text is available. The quality appraisal of the study was performed using The Critical Appraisal Skills Program (CASP) and The Joanna Briggs Institute (JBI) critical assessment tool. There were seven articles included in this review, with 440 total participants. There were two themes retrieved about barriers and support in practising SSC, including knowledge and medical conditions, both from the health staff’s side and the mother’s side. Future research is needed to review SSC implementation in midwife-led care units.